Effect of Frequency on Heat Spread by Interstitial Hypertemia Treatment Method for The Treatment of Sarcoma Tumors - Wahyudi, Slamet; Setyarini, Putu Hadi; Kretapaswakara, Isa Tan (International Journal of Integrated Engineering, 2023)
Frequency is a thing to calculate a wave. In biomedical science, frequency plays an important role in delivering heat as in bioheat transfer. In bioheat transfer studies, heat transfer in the human body can be used as one way of treatment such as therapy. At high temperatures that are usually above 40oC, the cell will die and cannot develop again this is called hyperthemia therapy. This therapy is commonly used in medicine with the function to kill tumor cells. There are 3 differences in hyperthemia therapy there are external, cavity and intersitital and interstitial hyperthermia therapy has better healing ability because heat is directly delivered to the tumor tissue to minimize tissue that no tumor is exposed to therapeutic temperature (40-46 oC). Then the author will conduct a study with an analysis of heat transfer carried out on five layers of the human body, namely the epidermis, dermis, fat, muscle, and bones by applying the interstitial method of hyperthermia therapy and influenced by frequencies with a value of 434; 915; 2450 MHz completed using finite element method with unsteady state conditions in two axial dimensions. This study showed that frequency affects the value of temperature distribution in the five layers of the body. The greater the frequency value given, the more easily distributed the temperature will be because the frequency will provide greater electromagnetic waves if the frequency is increased.